Would large scale farming be better than smallholder systems? - International Livestock Research Institute (International Livestock Research Institute, 2010)
Large scale systems can be more efficient but not always. Recorded at the ILRI Annual Program Meeting, Addis Ababa, 14-17 April 2010.